Isomer building blocks and K-forbidden decays. (12th April 2017) - Walker, P M
Abstract: High- K isomers are long-lived excitations of deformed atomic nuclei. Their structure is built from broken nucleon pairs that generate high angular momentum, K, along the nuclear symmetry axis. The partial conservation of this quantity leads to strong inhibition of electromagnetic decay, and hence to isomerism. The present work examines the hindrance factors for a range of multipole orders, with a focus on highly K -forbidden E 1 transitions from multi-quasiparticle isomers in the A ≈ 170 region of nuclei. Allowing for a general 10 4 inhibition of E 1 transitions, there is good accord with other multipole orders. A key feature is that the inhibition declines for isomers that are more highly excited, relative to a rigid rotor of the same total angular momentum. Comparison is also made with K -forbidden E 1 transitions in the quasicontinuum, and similar inhibition properties are found.